2018
DOI: 10.21767/2573-4466.100011
|View full text |Cite
|
Sign up to set email alerts
|

Application of Xylanase and β-Glucanase to Improve Nutrient Utilization in Poultry Fed Cereal Base Diets: Used of Enzymes in Poultry Diet

Abstract: The β-glucanases and xylanases have been used as feed additives for many years and their ability to improve the performance of poultry has been demonstrated in numerous publications. Starch, proteins, and lipids easily degraded in the bird's digestive systems, whereas the major parts of soluble and insoluble non-starch polysaccharides remain intact because of the lack of suitable enzymes. The positive nutritional effects achieved by the dietary supplementation of exogenous enzymes are proposed to be caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(38 reference statements)
1
7
0
1
Order By: Relevance
“…Treatment (2) AMEn (kcal kg -1 DM) Ileal digestibility coefficients on a dry matter basis (%) CP DM MM Ca P corn-soybean meal-based diets contain a lower amount of non-starch polysaccharides such as arabinoxylans and β-glucans (Stefanello et al, 2016;Slominski, 2011). This is important since the presence of a substrate affects enzyme action, with more expressive results expected when carbohydrates are supplemented in diets with a greater amount of substrate, such as those containing wheat, rye, and barley (Zarghi, 2018). The results of the present study are indicative of the positive action of the use of carbohydrases in association with hybrid phytase in diets based on corn and soybean meal, which allowed a reduction of 100 kcal kg -1 in diet composition, representing an extra contribution of 30 kcal kg -1 AMEn.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment (2) AMEn (kcal kg -1 DM) Ileal digestibility coefficients on a dry matter basis (%) CP DM MM Ca P corn-soybean meal-based diets contain a lower amount of non-starch polysaccharides such as arabinoxylans and β-glucans (Stefanello et al, 2016;Slominski, 2011). This is important since the presence of a substrate affects enzyme action, with more expressive results expected when carbohydrates are supplemented in diets with a greater amount of substrate, such as those containing wheat, rye, and barley (Zarghi, 2018). The results of the present study are indicative of the positive action of the use of carbohydrases in association with hybrid phytase in diets based on corn and soybean meal, which allowed a reduction of 100 kcal kg -1 in diet composition, representing an extra contribution of 30 kcal kg -1 AMEn.…”
Section: Resultsmentioning
confidence: 99%
“…Yadav and Jha demonstrated the linking of growth-promoting effects of enzymes with mucosal morphology of the small intestine [133]. Moreover, the increase in the membrane enzyme activity and role in the last step of digestion cause the reduction in crypt depth of jejunum, ultimately improving growth performance in chickens by xylanase supplementation in diet [134]. Exogenous protease plays an important role by reducing the undigested protein from diet or caudal gut inflammation reduction and maintaining tight junction integrity [135].…”
Section: Citric Acidmentioning
confidence: 99%
“…A number of studies have demonstrated that a combination of exogenous non-starch polysaccharide (NSP) enzymes and protease supplementation was used expectantly to improve growth performance and nutrient ultilization, and reduce nutrient excretion in broilers (9) and hens (7,10). The efficiency of exogenous enzyme combinations varied depending on dietary nutritional quality and substrate specificity (8,11). Responses to exogenous enzyme additions were expected to be greater in diets the lower ingredient quality and nutritional density (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%